About the eﬀectiveness of mastery of mathematical information - Ostapenko, A.; Januškevičienė, Olga (Lietuvos matematikos rinkinys, 2011)
Eﬀective interaction of students with information received in the lesson is the key to the success of mathematics teaching. Concrete methods in this direction are described in the article. The underlying thesis is the need for participation of the personality of teacher in this process.